Avaliação da expressão gênica da via STING em camundongos C57BL/6 submetidos a um modelo de clareamento de pelos com peróxido de hidrogênio (H2O2) e amônia (NH3) (banho de lua) e em pacientes com neoplasia mielodisplásica - Sampaio, Letícia Rodrigues (2023)
Reactive oxygen species (ROS), such as hydrogen peroxide, cause oxidative stress and genetic instability - a hallmark of cancer. The STING pathway works by recognizing double-stranded DNA fragments located in the cytoplasm, either by infectious agents or by genetic instability. In Brazil, there is a common practice of bleaching body hair and hair with products based on hydrogen peroxide and ammonia, which has been associated in clinical histories with the development of bone marrow neoplasms. The aim of the study was to evaluate the gene expression of the STING pathway in C57BL/6 mice subjected to body hair bleaching (skin hair bleanching) and in patients with Myelodysplastic Neoplasia. In the final experimental protocol, 35 male and 35 female C57BL/6 mice were topically intoxicated on the back with solutions of hydrogen peroxide and ammonia for 10 minutes, 1-2 times a week for 8-10 weeks. The following groups were examined: a) control group - 500µL of PBS (n = 7); b) peroxide group - intoxication with 500µL of a commercial formula of hydrogen peroxide (hydrogen peroxide) with a 12% concentration (40 volumes) (n = 7); c) acetylcysteine (NAC) control group - 500µL of PBS + saline solution (5mL/Kg, i. p) (n = 7); d) ammonia group - intoxication with 250µL of commercial hydrogen peroxide formula (hydrogen peroxide) with 12% concentration (40 volumes) + 250µL of commercial hair lightening formula based on ammonia at 5, 8% concentration (n = 7) and e) ammonia-acetylcysteine (NAC) group - intoxication with 250µL of commercial hydrogen peroxide formula (hydrogen peroxide) with 12% concentration (40 volumes) + 250µL of commercial hair lightening formula based on ammonia at 5.8% concentration + N-acetylcysteine (100mg/Kg, i. p) (n = 7). p) (n = 7). After euthanasia, the spleen was removed for gene expression analysis of the STING pathway and the femur was removed for cytogenetic and histopathological analysis. The cytogenetic study was carried out using G-banding, real-time PCR (RT-qPCR) was used for gene expression and histopathology was carried out by reading 5 fields under a 40x objective by two independent evaluators. No cytogenetic alterations were found in relation to exposure to ammonia or hydrogen peroxide. In the morphological analysis, mice in the peroxide group and the ammonia group showed hyperplasia of grouped megakaryocytes suggestive of myeloproliferative bone marrow disease. Gene expression analysis quantified the genes of the STING pathway: Cgas, Ddx41, Sting, Tbk1 and the Toll receptors Tlr3 and Tlr4. For male mice, the ammonia group showed greater expression of the Cgas gene than the NAC ammonia group (p = 0.035). With regard to the Sting gene, the mice in the peroxide group showed greater expression of Sting than the control group (p = 0.050) and the animals in the ammonia group showed greater expression of Sting than the animals in the NAC control (p = 0.050) and NAC ammonia (p = 0.050) groups. For the female mice, we observed that the animals in the peroxide group showed greater expression of Cgas than the animals in the control group (p = 0.047). In the cohort of patients with MDS, we found that DDX41 showed a higher level of expression in patients with a bone marrow blast count of more than 10% compared to patients who had ≤2% blasts and between 5% and 10% blasts (p=0.002 and p=0.037, respectively) and higher expression in patients with the MDS subtype with excess type-2 blasts (MDS-EB 2) compared to patients with the low-risk MDS-DM subtype (p=0.004). STING showed greater expression in patients with a bone marrow blast count between 5%-10% compared to patients with ≤2% blasts (p=0.016); greater expression in patients with the SMD-EB1 subtype compared to patients with the ring sideroblast subtype (p=0.013) and greater expression in patients with an altered karyotype (p=0.002). This research provided significant associations regarding STING expression, demonstrating that these genes may be deregulated by exposure to H2O2 and NH3 and in SMD, suggesting a possible link between exposure to these factors and the development of bone marrow neoplasia.